Long-term physico-chemical stability of 5-fluorouracile at standardised rounded doses (SRD) in MyFuser® portable infusion pump. (3rd October 2021) - Closset, Mélanie; Onorati, Sabrina; Colsoul, Marie-Lise; Goderniaux, Nicolas; Bihin, Benoît; Jamart, Jacques; Soumoy, Laura; Hecq, Jean-Daniel; Odou, Pascal; Galanti, Laurence
Abstract : Management of chemotherapies is a strategic issue for european healthcare. Dose-banding enables to reduce waiting time of patients in day care units and drug wastage. The aim of this study was to assess the stability of 5-Fluorouracile (5-FU) at standardised rounded doses of 4 and 5 g in MyFuser® portable infusion pump for in-advance preparation. Ten MyFuser® (4 and 5 gr 5-FU added to NaCl 0.9%) were prepared under aseptic conditions and stored at room temperature (23 ± 2 °C) for 28 days then at 30 °C for three days. Physical stability tests were periodically performed: visual and microscopic inspection, pH measurements and optical densities. The concentration of solutions was measured by High Performance Liquid Chromatography/UV detector. Results confirm the stability of 5-FU at selected SRD of 4 g and 5 g with NaCl 0.9% in MyFuser® for at least 28 days at room temperature and three days at 30 °C, allowing in-advance preparation.